PAIN MANAGEMENT IN PRIMARY DYSMENORRHOEA AND ENDOMETRIOSIS- AYURVEDIC PERSPECTIVE - Asitha.H (International Journal of Ayurveda and Pharma Research, 2021)
Pain is generally described as an unpleasant sensation and a universally understood sign of disease. Around 80% of women experience pain during periods from adolescent period right up to menopause. Dysmenorrhoea literally means painful menstruation. Primary dysmenorrhoea is one where there is no identifiable pelvic pathology. The pain begins a few hours before or just with the onset of menstruation and lasts for 24-48 hours. Secondary dysmenorrhoea is normally considered to be menstruation –associated pain occurring in the presence of pelvic pathology. Pain starts 7-8 days before menstruation. Endometriosis is one of the main causes of secondary dysmenorrhoea. Dysmenorrhoea can be correlated to Udavarta and endometriosis to Vatiki. In Udavarta, Sanga and Vimargagamana of Vata and derangement of Kapha pitta is responsible for pain. In Vatiki there is Apana vata vimargagamana, Vyana vata and Pitta vitiation causes Artava dusti and Dusta artava sthana samsraya in Kha vaigunya sites. So administration of drugs and treatment modalities crackling these factors involved in the etiopathogenesis do the work. Ayurvedic classic textbook along with available modern literatures were referred to make a clear view regarding the concept of pain and the main Yonirogas causing pain during menstruation and its management.